Variant O89 O-Antigen of E. coli Is Associated With Group 1 Capsule Loci and Multidrug Resistance - Harris, Susan; Piotrowska, Marta J.; Goldstone, Robert J.; Qi, Ruby; Foster, Geoffrey; Dobrindt, Ulrich; Madec, Jean-Yves; Valat, Charlotte; Rao, Francesco V.; Smith, David G. E. (Frontiers in Microbiology, 2018)
Bacterial surface polysaccharides play significant roles in fitness and virulence. In Gram-negative bacteria such as Escherichia coli, major surface polysaccharides are lipopolysaccharide and capsule, representing O- and K-antigens respectively. There are multiple combinations of O:K types, many of which are well-characterised and can be related to ecotype or pathotype. In this investigation we have identified a novel O:K permutation resulting through a process of major genome reorganisation in a clade of E. coli. A multidrug-resistant, extended-spectrum β-lactamase (ESBL)-producing strain – E. coli 26561 – represented a prototype of strains combining a locus variant of O89 and group I capsular polysaccharide. Specifically, the variant O89 locus in this strain was truncated at gnd, flanked by insertion sequences and located between nfsB and ybdK and we apply the term O89m for this variant. The prototype lacked colanic acid and O-antigen loci between yegH and hisI with this tandem polysaccharide locus being replaced with a group I capsule (G1C) which, rather than being a recognised E. coli capsule type, this locus matched to Klebsiella K10 capsule type. A genomic survey identified more than 200 E. coli strains which possessed the O89m locus variant with one of a variety of G1C types. Isolates from our collection with the combination of O89m and G1C all displayed a mucoid phenotype and E. coli 26561 was unusual in exhibiting a mucoviscous phenotype more recognised as a characteristic among Klebsiella strains. Despite the locus truncation and novel location, all O89m:G1C strains examined showed a ladder pattern typifying smooth lipopolysaccharide and also showed high molecular weight, alcian blue-staining polysaccharide in cellular and/or extra-cellular fractions. Expression of both O-antigen and capsule biosynthesis loci were confirmed in prototype strain 26561 through quantitative proteome analysis. Further in silico exploration of more than 200 E. coli strains possessing the O89m:G1C combination identified a very high prevalence of multidrug resistance (MDR) –85% possessed resistance to three or more antibiotic classes and a high proportion (58%) of these carried ESBL and/or carbapenemase. The increasing isolation of O89m:G1C isolates from extra-intestinal infection sites suggests that these represents an emergent clade of invasive, MDR E. coli.